Effect of conservation tillage, residue and nitrogen levels on soil nitrogen fractions and their contributions in nitrogen uptake in castor (Ricinus communis) - CHANDRIKA, D SUMA; SHARMA, K L; VIDYAVATHI, S; MUNNALAL,; KUMAR, T SATISH; RANI, K USHA (The Indian Journal of Agricultural Sciences, 2016)
This experiment was conducted in rainfed semi-arid tropical Alfisol at Hayathnagar Research Farm of Central Research Institute for Dryland Agriculture, Hyderabad, India, during the period 1995 to 2014 to study the long-term effect of conservation agricultural practices on organic and inorganic N fractions in soil, their contribution to available N pool and N uptake in castor (Ricinus communis L.). The experiment was conducted in a strip split-split plot design with conventional tillage (CT) and minimum tillage (MT) as main factors, surface application of sorghum stover @ 2 tonnes/ha (SS), fresh gliricidia loppings @ 2 tonnes/ha (GL) and ‘no’ residue (NR) as sub-factors and levels of N, viz. 0 (N0), 30 (N30), 60 (N60) and 90 (N90) kg N/ha as sub-sub factors. The results of the study revealed that increasing N levels influenced exchangeable ammonical N and nitrate N. Practice of conservation tillage, application of residues and nitrogen significantly influenced the hydrolysable organic N fractions in the soil. Among these, aminoacid N, hexosamine N, hydrolyzable NH 4 + and unidentified N constituted 52%, 8%, 13% and 27% of total hydrolysable N. Linear regression relationship between castor yield and total soil N and N uptake (R2 = 0.998) was found significant. Further, inter correlations between N fractions indicated free mobility among the N fractions. Hence, the build up of N in these pools can be significantly influenced by adoption of appropriate conservation agricultural practices on long term basis in rainfed Alfisols which are highly deficient in available soil N.